Long term variations of atmospheric synoptic variability: A study based on radiosonde data from Lindenberg (Germany) - Martin Göber; Andreas Hense (Meteorologische Zeitschrift, 1995)
In an extension of a study by Fraedrich et al. (1979a, b) we show how the atmospheric processes generating a local climate state can vary from year to year and between two decades in Eastern Germany - an area which is frequently visited by mature cyclones. On the basis of homogeneous and long (1971- 90) time series of 4 times daily radiosonde ascents of the GDR we investigated the interannual variability of monthly means, synoptic variability (variance/covariance with periods between 2 and 8 days, "weather"), low frequency variability (periods of 10-30 days), and high frequency variability (periods of less than one day, "noise") of geopotential, temperature, zonal and meridional wind and specific humidity at 14 levels between 925 and 50 hPa. For the time interval 1971-90 we find that the already described significant increase of monthly mean tropospheric temperature and mean zonal wind is accompanied both by changes of different transports carried out by the time mean circulation and by significant changes of monthly variances and transports by eddies of different scales. Additionally we suggest for further studies of interannual variability of atmospheric processes based on radiosonde data applying a low pass filter on the data removing fluctuations with a period of less than one day before making any further operation with the data.